1992
DOI: 10.1002/anie.199206361
|View full text |Cite
|
Sign up to set email alerts
|

Proof of the Catalytic Activity of a Naked Metal Cluster in the Gas Phase

Abstract: An experiment with five steps within a mass spectrometer (labeled MSn) showed that in the gas phase the naked Fe 4+ ion forms the molecule C6H6, probably benzene, from ethene via [Fe4(C2H2)m]+ complexes (m = 1–4), and thus acts as a catalytic center. The MS1–MS5 steps of the complex experiment are sketched below. CID = collision‐induced deactivation, a = isolation, m = 1–3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 20 publications
1
32
0
3
Order By: Relevance
“…They have demonstrated that benzene could be formed from ethylene under hydrogen abstraction and from cyclopropane on Fe 4 ϩ . [1][2][3][4] The formation of benzene has also been observed in the gas phase from acetylene on Fe ϩ and from ethylene on W ϩ and U ϩ . [5][6][7][8][9] Various hypotheses have been formulated to explain what is going on, but a detailed mechanism is not available yet.…”
Section: Introductionmentioning
confidence: 87%
“…They have demonstrated that benzene could be formed from ethylene under hydrogen abstraction and from cyclopropane on Fe 4 ϩ . [1][2][3][4] The formation of benzene has also been observed in the gas phase from acetylene on Fe ϩ and from ethylene on W ϩ and U ϩ . [5][6][7][8][9] Various hypotheses have been formulated to explain what is going on, but a detailed mechanism is not available yet.…”
Section: Introductionmentioning
confidence: 87%
“…The first investigations on the catalytic activity of metal cluster ions have been carried out in an ion cyclotron resonance mass spectrometer by Irion and co-workers [56]. They demonstrated the conversion of ethylene to benzene by Fe 4 + cluster cations.…”
Section: Catalysis With Free Metal Clustersmentioning
confidence: 99%
“…Taking into account that the rate of CO dissociation from RhVO 3 CO À is rather low at the highest temperature (ca. 600 K; Supporting Information, Table S6) that was accessible in our experiment, the collision-induced dissociation (CID) technique that had been extensively employed to establish catalytic reactions relevant with other small molecules [18] was employed to regenerate RhVO 3 À cluster.T he CID experiments of massselected RhVO 3 CO À anions with Ar in the collision cell under single collision conditions characterized two new product ions of RhVO 3 À and VO 3 À ,c orresponding to the elimination of CO and RhCO,r espectively ( Supporting Information, Figure S6):…”
Section: Angewandte Chemiementioning
confidence: 99%